2014
DOI: 10.1188/15.onf.15-22
|View full text |Cite
|
Sign up to set email alerts
|

Empowering <i>Promotores de Salud</i> as Partners in Cancer Education and Research in Rural Southwest Kansas

Abstract: Purpose/Objectives To describe community-based participatory processes used to develop promotore training on cancer research, and to assess the feasibility of training promotores from rural communities to disseminate cancer research information. Design Prospective, cohort design. Setting Rural communities in the state of Kansas. Sample 34 Spanish-speaking promotores attended an information session; 27 enrolled and 22 completed training. Methods With input from a community advisory board, the authors de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…1). On two occasions, we identified two articles that present data on the same study [44][45][46][47] , for a total of 16 unique studies (Table 1); these included 13 interventional studies (Table 2) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and three observational studies (Table 3). [59][60][61] Studies addressed the four levels of the health care system and engaged patients (n = 7), community members (n = 8), and family members (n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). On two occasions, we identified two articles that present data on the same study [44][45][46][47] , for a total of 16 unique studies (Table 1); these included 13 interventional studies (Table 2) [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] and three observational studies (Table 3). [59][60][61] Studies addressed the four levels of the health care system and engaged patients (n = 7), community members (n = 8), and family members (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Engagement took the form of groups of patients, family members, or community members only 44,50,52,56,57 ; or groups that also involved staff or clinicians 53,55,58 ; in four studies, these two strategies were compared. [46][47][48][49]51 Two studies engaged groups that speak non-dominant languages: one involved indigenous communities in India 44 and one involved Spanish-speaking immigrants in the USA.…”
Section: Organizational Makeup Recruitment Strategies and Levels Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…4,11 Research suggests that when providing information on preventative measures, cancer, and disease management, CHWs are effective in helping community members navigate the health-care system and overcome distrust of health-care professionals. 12,13 CHWs, also known as “promotoras de salud” in the Hispanic and Latino community, are “of the community” and therefore, well-positioned to reach other community members who may not otherwise pursue help or information about their health.…”
Section: Community Health Workersmentioning
confidence: 99%
“…Further, this study revealed that Latino individuals prefer interventions which occur outside of the clinical setting. Cupertino et al (2015) trained 22 Latino lay health workers from rural parts of Kansas in cancer and research ethics. These investigators concluded that it was feasible to engage lay health workers to deliver community-based cancer education and serve as an important adjunct to clinicians in underserved, rural communities.…”
Section: Introductionmentioning
confidence: 99%